Effect of natural gel product on bovine dentin erosion in vitro - Andre de Carvalho SALES-PERES; Juliane Avansini MARSICANO; Rudan Paraiso GARCIA; Moacir Rossi FORIM; Maria Fatima das Gracas Fernandes da SILVA; Silvia Helena de Carvalho SALES-PERES (University of São Paulo, 2013)
Objective: To evaluate the efficacy of Neem (Azadirachta indica) experimental gel for the prevention of erosive wear on bovine dentin, in vitro. Material and Methods: One hundred dentin blocks were allocated into 5 experimental groups (20 samples each): C (control group, without gel); CG (control group, only base gel); F (fluoride gel, 1.23% NaF; pH 4.1, Dentsply; Brazil); N (Neem gel, 10% neem extract; pH 4.1, manipulation); NF (Neem+fluoride gel, 10% Neem extract and 1.23% NaF; pH 4.1, manipulation). The blocks were stored in artificial saliva for 24 hours. After this, they were submitted to six alternating re- and demineralization cycles. The blocks were analyzed for wear (profilometry). The results were submitted to statistical analysis by ANOVA and Tukey tests (P<0.05). Results: The mean wear (±SD, µm) was shown as follows in groups: C (13.09±0.99), CG (10.60±1.99), F (10.90±1.44), N (12.68±1.13) and NF (10.84±1.65). All gels showed some preventive action when compared with control group. However, significant differences were found only between Neem+fluoride gel and fluoride gel. Conclusion: A single application of a neem-containing fluoride gel reduced dentin erosion, thus it is a possible alternative in reducing dental wear. Further research should investigate the action mechanism and the synergism between them.